Canales de comunicación organizacional interna en el Distrito de Educación 13D12 Tosagua-Rocafuerte 2021-2022 - Barre Angulo, Víctor Alejandro (2023)
The objective of this work was to evaluate the internal organizational communication channels to identify the influence on administrative management in the Education District 13D12 Tosagua - Rocafuerte 2021-2022. The inductive and analytical methods that facilitated the research process were used as methods, allowing the use of thought to execute deductions, analysis and synthesis, in the same way the survey and interview were used as techniques that served to approach the facts and access information. the collection of information. The results show that the organizational communication channels and the administrative management in the district are at a medium level, identifying deficiencies in the dimensions of openness, flexibility and multidirectionality, while instrumentalization is at an optimal level. It is concluded that there is a clear deficit in the current state of the internal organizational communication channels in the Education District 13D12 Tosagua-Rocafuerte, determining that they are at a medium level. This supposes a decrease in the dimensions of opening, flexibility and multidirectionality. However, the instrumentalization is at an optimal level.